Teacher's perspective on how the MBG program affects students' motivation to learn - Firman Firman; Hety Diana Septika; Fara Virgianita Pangandongan; Muhlis Muhlis (Himpunan Pengembang Kurikulum Indonesia, 2026)
The Makan Bergizi Gratis (MBG) Program is a government policy aimed at supporting the fulfillment of students' food and nutritional needs so they can carry out their activities well. This study was conducted to address the gap in the literature regarding teachers' roles as implementers and primary observers of MBG's impact on students' learning behavior. This study aims to analyze teachers' perceptions of the MBG program using the Health Belief Model (HBM) and to examine the implications for students' motivation to learn. This study employed a qualitative approach using a transcendental phenomenological design. Data collection techniques included in-depth interviews, observations, and documentation of six (6) class teachers at SDN 015 Samarinda Ulu, SDN 018 Samarinda Ulu, and SD Al-Firdaus. The results showed that teachers viewed MBG as positively impacting the fulfillment of students' food needs, especially for students who are not accustomed to breakfast and come from underprivileged families. The impact of MBG on learning motivation is contextual, positive in underprivileged schools and neutral in schools with independent nutrition ecosystems. The program's implementation still faces obstacles, including menu variations, teacher workload, and coordination. However, teachers continue to support the program's sustainability with notes. Abstrak Program Makan Bergizi Gratis (MBG) merupakan kebijakan pemerintah yang ditujukan untuk mendukung pemenuhan kebutuhan pangan dan gizi murid agar dapat beraktivitas dengan baik. Penelitian ini dilakukan untuk mengisi celah literatur mengenai peran guru sebagai pelaksana sekaligus pengamat utama terhadap dampak MBG pada perilaku belajar murid. Penelitian ini bertujuan untuk menganalisis persepsi guru terhadap program MBG menggunakan teori Health Belief Model (HBM), serta implikasinya terhadap motivasi belajar murid. Penelitian ini menggunakan metode kualitatif dengan desain fenomenologi transendental. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi terhadap enam (6) guru kelas di SDN 015 Samarinda Ulu, SDN 018 Samarinda Ulu, dan SD Al-Firdaus. Hasil penelitian menunjukkan bahwa guru memandang MBG dapat memberikan dampak positif dalam mendukung pemenuhan kebutuhan pangan murid, terutama bagi murid yang tidak terbiasa sarapan dan berasal dari keluarga prasejahtera. Dampak MBG terhadap motivasi belajar bersifat kontekstual, positif pada sekolah prasejahtera dan netral pada sekolah dengan ekosistem nutrisi mandiri. Pelaksanaan program masih menghadapi kendala berupa variasi menu, beban kerja guru, dan koordinasi. Namun, guru tetap mendukung keberlanjutan program dengan catatan. Kata Kunci: health belief model; makan bergizi gratis; motivasi belajar; persepsi guru; sekolah dasar